Application of waste cashew nut shell ash showed significant reduction in mobility of Pb and Cd in waste battery contaminated soil (2011)
Increases in ore mining, metal smelting activities, and several other industrial practices in recent times have brought about contamination of soils at higher levels; these have prompted concerns on the consequent effects on the local and global ecosystem. Various remediation technologies have often been sought to meet the challenges. This study therefore seeks to assess the potential of cashew nut shell (CNS) ash for immobilizing Cd and Pb in battery contaminated soil. The ash samples used for the study were obtained from a waste cashew nut shell burning site, Olowopokun, Iseyin L.G.A of Oyo State, Nigeria. Some soil samples and sediments from a nearby stream at this site were taken. Soil samples were also taken from battery-contaminated dumpsites at Ile-Igbon, Lalupon, Oke-Omi, and Ikumapayi, in Lagelu L.G.A of Oyo State. One gram each of ground soil samples, ash and sediment were analyzed for heavy metals contents. Ash generated from waste cashew nut shell from cashew nut processing company dumpsite were mixed with contaminated soil samples from the lead battery dumpsite at ratios 10:1.5 and 10:3.0. The amended and un-amended soil samples were subjected to TCLP in accordance with US Environmental Protection Agency (USEPA) Method 1311. Cd gave 97% efficiency in the reduction of its mobility in the amended soil while Pb gave 80% efficiency. Increase in the quantity of CNS ash used for amendment from ratio 10:1 to 10:2 caused a rise in the pH of the soil, this translated to further reduction of the leached Pb and Cd from the soil. The assessment of the mobility of Pb and Cd in the soil as induced by the addition of CNS ash showed that there was reduction in the mobility of Pb and Cd from the contaminated soil samples as assessed by TCLP procedure. The use of the CNS ash in stabilizing the contaminated soil served as an effective waste disposal method for waste CNS as well as source for remediation of contaminated soil. Waste CNS ash could be a great source for in-situ remediation of contaminated soil.